Ответы и объяснения

Лучший Ответ!
2013-11-08T22:38:02+04:00
2)4^ x^{2} -3*2^ x^{2} +2=0;                                                                                            2^2*2^ x^{2} -3*2^ x^{2} +2=0                                                                                      2^ x^{2} (4-3+2)=0                                                                                                     2^ x^{2} *3=0                                                                                                             2^ x^{2} =2^0                                                                                                              x^{2} =1                                                                                                                    х=-1;1